The Pattern of Albumin Consumption in Teaching University Hospitals in Northeastern Iran: Albumin Consumption - Mollazadeh, Samaneh; Tavanaei Tamanaei, Taraneh; Oghazian, Sahar; Oghazian, Sabah; Oghazian, Mohammad Bagher (Iranian Journal of Pharmaceutical Sciences, 2021)
Insufficient information on accurate indications of albumin administrations and the lack of acceptable protocols emphasize the importance of performing further studies on the albumin consumption. So, the current study aimed to explore the albumin administration in the teaching hospitals to not only provide an effective pattern, but also to provide low-cost strategies for rational use of this drug. Herein, one hundred patients were given albumin during the study period, who were randomly selected from hospitals affiliated with a large public university. The collected data were analyzed using IBM SPSS Statistics (version 22). Our findings showed that 46% of the patients finally received albumin in terms of the approved guideline. In total, 777 albumin vials were used for 100 cases, for whom 414 vials (53.2%) were rationally prescribed. The albumin was frequently administrated in the ICU wards with 62% of total vials. In accordance with some previous studies, our results demonstrated that most of the albumins were prescribed inappropriately, which impose high-cost on the patients as well as on health care system. Therefore, long-term monitoring of albumin therapy implemented by trained physicians, is suggested to promote rational albumin consumption.